A review of autonomous vehicle technology landscape. (27th September 2019) - Divakarla, Kavya P.; Emadi, Ali; Razavi, Saiedeh; Habibi, Saeid; Yan, Fengjun
The automotive industry is seen to be making a monumental paradigm shift from manual to semi-autonomous to fully autonomous vehicles. As such, this paper attempts to offer an overview of some of the major aspects associated with an autonomous vehicle. The demand for autonomous vehicles has grown tremendously with the increasing number of road accidents caused due to driver distraction. Based on the level of autonomy within vehicles, it is possible to either have autonomous systems that will just assist the driver for safe operation of the vehicle or could take over the complete control of the vehicle. Autonomous vehicles seem to have numerous advantages for road safety, traffic optimisation, military or medical applications where only minimal human intervention is desirable and so on. This paper attempts to highlight the vast majority of vital and most relevant topics emerging in the field of autonomous vehicle technology.